Interdisciplinarity in Mathematics through Meaningful Learning - Passos, Ana Paula (2021)
The article presents a summary of the research conducted in 2019 as a Final Work for obtaining the title of Master in Science and Mathematics Teaching. This research aims to verify that the interdisciplinary stance in the Teaching and Learning Process in Mathematics in High School favors the assimilation and contextualization of the Square Function content, based on Ausubel's Theory of Significant Learning and the conceptions of Interdisciplinarity of Hilton Japiassu and Ivani Fazenda. It sought to develop interdisciplinarity from the Squared Function content with other areas of knowledge, highlighting the applicability of interdisciplinary learning in Physics through Problem Solving. A qualitative case study was carried out considering a sample of thirty regular high school students in a state school located in the city of Manaus/AM. The instruments used for data collection were: questionnaires, semi-structured interviews and participant observation. The results showed the difficulties of implementing the interdisciplinary practice in the daily pedagogical routine, due to factors such as: difficulties of inter-relationship between the contents, lack of pedagogical support, among others.